A theoretical study of condensation heat transfer in tubes with novel cross-sections - Lee, Y. W. (2023)
This paper presents a numerical study of stratified flow condensation heat transfer in tubes with novel cross-section designs. A design framework of the novel cross-section geometry was developed by first studying and analyzing the condensate film distribution in a circular tube. It was found that the circular arc diameter and orientation have effects on the condensate film thickness. Based on this understanding, four different cross-section designs (models N1, N2, N3 and N4) formed by connecting circular arcs of different curvatures at various orientations were proposed. The heat transfer performances of these models were compared to a circular tube of the same perimeter. Our simulations show that all models possess higher average heat transfer coefficients than a circular tube when no accumulated condensate layer is present. Among all the models proposed, model N4 exhibits the largest heat transfer enhancement ratio of 1.42 at ∊ = 0.96. The design of model N4 utilizes small circular arcs which are arranged in an orientation that increases the effect of the gravitational force, providing significant condensate film thickness reduction over a large area. This study not only demonstrates the possibility of enhancing condensation heat transfer by simply varying the tube curvature but also provided a design guideline which can be employed for the development of novel cross-section tubes that can be fabricated by advanced manufacturing techniques such as selective laser melting.